PHYSIOTHERAPY MANAGEMENT IN SPRAIN CASES DEXTRA ANKLE AT EFARINA HOSPITAL PEMATANGSIANTAR - Marolop Parlindungan Napitu; Yeni Trisna Purba; Desri Friti Anita Purba; Alexander Marbun (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Sprain ankle area injuries to the joints, with ligament tears resulting from sudden excessive stress or repeated excessive use of the joints. In general, sprain due to falls, slips, or pressure on the body that causes bones in the joints to shift, causing impaired ankle stability. Ankle sprain occurs due to muscle weakness and ligament weakness by strengthening muscle training and increasing LGS using exercise therapy, and can help and improve muscle weakness caused by complex lateral ligament damage. The purpose of this thesis is to determine the effectiveness and exercise therapy in ankle sprain patients. In the case study, patients were found to have pain while standing on one foot on their right foot, and the patient felt uncomfortable when leaning on running because of pain that disturbed his balance. Physiotherapy interventions for patients were ultrasound and exercise therapy is given in stages over 3 days. After doing a gradual exercise program for 3 days. To obtain optimal therapeutic results, good collaboration between physiotherapy and sufferers is needed so that maximum results can be obtained. Independent exercise that is done regularly by the patient and is effective therapy to increase muscle strength and increase muscle flexibility.